The exploration of miRNAs and mRNA profiles revealed the molecular mechanisms of cattle-yak male infertility - Zhao, Shaokang; Sun, Wenqiang; Chen, Shi-Yi; Li, Yuchao; Wang, Jie; Lai, Songjia; Jia, Xianbo (Frontiers in Veterinary Science, 2022)
Cattle-yak, the first-generation offspring of cattle and yak, inherited many excellent characteristics from their parents. However, F1 male hybrid infertility restricts the utilization of heterosis greatly. In this study, we first compared the testicular tissues histological characteristics of three cattle, three yaks and three cattle-yak. Then we analyzed the miRNA profiles and the targets function of nine samples with RNA-seq technology. We further analyzed the function of DE gene sets of mRNA profiles identified previously with GSEA. Testicular histology indicated that the seminiferous tubules became vacuolated and there are few active germs cells can be seen. RNA-seq results showed 47 up-regulated and 34 down-regulated, 16 up-regulated and 21 down-regulated miRNAs in cattle and yaks compared with cattle-yak, respectively. In addition, the miRNA down-regulated in cattle-yak bta-miR-7 and its target candidates MYRFL, FANCA, INSL3, USP9X, SHF may related to the reproductive progress. With the further network analysis, we screened such hub genes and function terms. GSE GO and GSE KEGG displayed that the DE gene sets most enriched in ATP binding, DNA binding, reproduction process. Our study is important for explaining the molecular mechanism of cattle-yak infertility.